Examining Faculty Perspectives on the Role and Value of Intercollegiate Athletics - Harry, Molly; Springer, Daniel (Journal of Intercollegiate Sport, 2024)
The uneasy marriage of higher education and athletics can be seen through the conceptual lenses of former institution and National Collegiate Athletic Association (NCAA) President Myles Brand’s Standard or Integrated View. The Standard View maintains that athletics serves as a business while the Integrated View argues that athletics should be appreciated as a form of education and art. Through these perspectives of athletics as a business, education, and art, this study surveyed faculty at one football bowl subdivision institution (n = 216) on their perceptions of athletics. Analyses demonstrated faculty perceptions were varied and contradictory as they noted athletics was simultaneously a business important for their institution, but also a detractor for higher education at large. Additionally, they perceived some developmental benefits of participation in athletics but still did not believe sports to be educational in nature. Implications for better understanding faculty perceptions of athletics while improving the education-sport marriage are discussed.